Penggunaan Internet Marketing Dalam Bentuk Brand Association Pada Penelitian Langkok Kuliner Pasaman Barat - Nadifa Rahma Putri (Sadida Islamic Communications and Media Studies, 2021)
This research is entitled "the use of internet marketing in the form of a brand association in West Pasaman culinary langkok research" to find out how to use internet marketing in marketing the culinary langkok business and to know the importance of brand association in a business. This research is a descriptive study with a qualitative approach and data collection by collecting data from informants by interviewing and visiting places and reading articles about culinary arts. This study discusses internet marketing, what is a brand association, marketing using culinary langkok internet marketing.